2022
DOI: 10.1038/s41380-022-01772-8
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in cognitively unimpaired older adults are associated with lower structural and functional integrity in a frontolimbic network

Abstract: Subclinical depressive symptoms are associated with increased risk of Alzheimer’s disease (AD), but the brain mechanisms underlying this relationship are still unclear. We aimed to provide a comprehensive overview of the brain substrates of subclinical depressive symptoms in cognitively unimpaired older adults using complementary multimodal neuroimaging data. We included cognitively unimpaired older adults from the baseline data of the primary cohort Age-Well (n = 135), and from the replication cohort ADNI (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 92 publications
5
23
0
Order By: Relevance
“…It is notable that the relationship between cerebrovascular disease and depressive symptoms is present at the level of subthreshold depression. This result is consistent with findings from the broader literature indicating that individuals with subthreshold depression experience white matter microstructural changes 50,51 and WMHs 52 similar to those observed in major depressive disorder, and have greater functional impairment (e.g., impairment in activities of daily living) 53 and increased risk of mortality compared to their healthy, same-aged peers. 54 Subthreshold depressive symptoms have also recently been linked to the presence of clinical vascular conditions in mid-to-late life, including elevated blood pressure variability 55 and an estimate of overall cardiovascular health that includes modifiable vascular risk factors such as body weight, blood glucose, total cholesterol, blood pressure, and frequency of physical activity.…”
Section: Ces-dsupporting
confidence: 90%
“…It is notable that the relationship between cerebrovascular disease and depressive symptoms is present at the level of subthreshold depression. This result is consistent with findings from the broader literature indicating that individuals with subthreshold depression experience white matter microstructural changes 50,51 and WMHs 52 similar to those observed in major depressive disorder, and have greater functional impairment (e.g., impairment in activities of daily living) 53 and increased risk of mortality compared to their healthy, same-aged peers. 54 Subthreshold depressive symptoms have also recently been linked to the presence of clinical vascular conditions in mid-to-late life, including elevated blood pressure variability 55 and an estimate of overall cardiovascular health that includes modifiable vascular risk factors such as body weight, blood glucose, total cholesterol, blood pressure, and frequency of physical activity.…”
Section: Ces-dsupporting
confidence: 90%
“…In our study, we found a significant reduction in 5-HT innervation of the EC, and since these 5-HT neurons project to other cortical regions there is likely 5-HT denervation in the PFC and OFC as well. The EC, PFC, cingulate, insula and temporoparietal cortex have all been implicated with depression and negative affect in older adults [ 75 , 76 ], so loss of 5-HT input to any one of these regions may be sufficient to drive depression in AD.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Moreover, a recent study reported that subclinical depressive symptoms are not associated with brain amyloidosis in cognitively healthy older adults. [25] This could result in a lower risk of developing Alzheimer's disease dementia in the Psy subgroup.…”
Section: Discussionmentioning
confidence: 99%